ANALISA BIAYA STANDAR DAN PENGENDALIAN BIAYA TENAGA KERJA LANGSUNG PADA PT. DRYDOCKS WORLD PAXOCEAN DI KOTA BATAM - Panggabean, Rista Bernike; Hamidi, Hamidi; Salesti, Jayana (Universitas Riau Kepulauan, 2016)
The research was conducted in PAXOCEAN DRYDOCKS WORLD to know whether the establishment of a standard direct labor costs as a means of cost control being effectively and efficiently on behalf of the company. The results of this research show the calculation method analysis of direct wage rates and variansi methods of analysis variansi the number of direct labor hours in the period June suffered losses amounting to Rp1.317.365 or 2,51% of standard fee with total actual hours of work amounted to 3.915. Whereas with the same calculation method analysis on period of July had profit of Rp 2.104.517,52 or 4.88 out of standard costs with actual working hours amounting to 4.686 .5 hours. The conclusion is based on calculation and analysis that has been done the writer can say in standard costing PT Drydocks World Paxocean has been set up properly and in accordance with what is happening and with standard costing is good then the use of the standard fee as a means of controlling the cost of direct labor can be said to be effective and efficient. Keywords: Standard Costs, Direct Labor Cost Control